2007
DOI: 10.1086/518895
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Dynamics during Natural Infection Are Associated with Long‐Term Histological Outcome of Chronic Hepatitis C Disease

Abstract: Histological progression of hepatitis C is tightly associated with homogenization of HCV quasispecies, perhaps reflecting immune failure and/or selective outgrowth of aggressive viral variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 50 publications
4
46
1
Order By: Relevance
“…Observation of the reduction in quasispecies diversity associated with severity of liver disease (38,50) may be interpreted in terms of variation in virulence during stages 3 and 4 of HCV infection. It is also conceivable that sequence variants prevalent at different stages of infection may have somewhat specific immunological properties, which may be explored for the development of hepatitis C prophylactic or therapeutic vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Observation of the reduction in quasispecies diversity associated with severity of liver disease (38,50) may be interpreted in terms of variation in virulence during stages 3 and 4 of HCV infection. It is also conceivable that sequence variants prevalent at different stages of infection may have somewhat specific immunological properties, which may be explored for the development of hepatitis C prophylactic or therapeutic vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…These replacements may begin with a cloud of closely related virus strains (i.e., intrahost viral diversity), generated in part by the error-prone RNA-dependent RNA polymerase of DENV (15,16). The intrahost diversity of viruses is typically described in chronic infections, such as those caused by HIV and hepatitis C virus (17)(18)(19), but has also been found in acute infections with DENV and other RNA viruses (20)(21)(22)(23). During arbovirus infections, such populations are subject to natural selection in both the mosquito and the human host.…”
mentioning
confidence: 99%
“…Studies of mumps virus and poliovirus demonstrated that increases in the genetic heterogeneity of the virus population led to increases in pathogenesis (28,32). In contrast, a high level of variation in the population of hepatitis C virus and WNV has been associated with decreases in pathogenesis (16,31). In addition, studies using a mouse model of foot and mouth disease virus pathogenesis suggested that the overall pathogenic potential of a virus population arises through a complex interplay of viral genomes that differ in their individual potential to cause disease (27).…”
mentioning
confidence: 99%